Performance Analysis of HRO-B+ Scheme for the Nested Mobile Networks using OPNet - Shayma Senan; Aisha Hassan A. Hashim (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
As a demand of accessing Internet is increasing dramatically, host mobility becomes insufficient to fulfill these requirements. However, to overcome this limitation, network mobility has been introduced. One of its implementation is NEMO Basic Support protocol which is proposed by Internet Engineering Task Force (IETF). In NEMO, one or more Mobile Router(s) manages the mobility of the network in a way that its nodes would be unaware of their movement. Although, it provides several advantages, it lacks many drawbacks in term of route optimization especially when multiple nested mobile networks are formed. This paper presents a new hierarchical route optimization scheme for nested mobile networks using Advanced Binding Update List (BUL+), which is called HRO-B+. From performance evaluation, it shows that this scheme performs better in terms of throughput, delay, response time, and traffic, and achieves optimal routing.